DEVELOPMENT OF EDUCATION RETURN RATE IN EAST JAVA 2015 AND 2018 - Nuelda Amalia; Lilik Sugiharti (East Java Economic Journal, 2019)
Education provides many benefits for the workforce, one of which is income when enter-ing the labor market. The return on educational benefits as measured by income is often referred to as the rate of return on education investment. This study aims to determinethe development of the rate of return on education investment in East Java in 2015 and2018. The data used are data from the East Java National Labor Force Survey (Sakernas) in2015 and 2018. The estimated rate of return on education investment is carried out usingthe Heckman Selection Model Method which uses the Heckman Selection Model. modifiedMincer’s Income Function Model to overcome sample-selectivity-bias. The result is thatthe rate of return on investment in education in East Java in 2015 and 2018 generallyincreased, except at the higher education level.Keywords: Return on Investment Education, Income, Profitability, East JavaJEL : I26, I25, N35